ANALISIS TINDAK TUTUR DIREKTIF ANAK USIA PRASEKOLAH DI LINGKUNGAN BERMAIN - Faturrohman, Aji; Rusminto, Nurlaksana Eko; Munaris, Munaris; Widodo, Mulyanto; Samhati, Siti (Universitas Hamzanwadi, 2024)
The importance of analyzing directive speech acts in preschool-aged children needs to be carried out to see how preschool-aged children act. At pre-school age, children experience rapid language development. Understanding the speech acts of pre-school children helps parents and educators support the language learning process effectively. The research was conducted at Timezone Lampung City Mall, this research data is directive speech acts of preschool children aged 5-6 years. The research subjects were children aged 5-6 years who played at Timezone Lampung City Mall. Based on the results, it can be seen that the forms of directive speech acts found in preschool children (5-6 years) at Timezone Lampung City Mall are in the form of requests, questions, commands, prohibitions and advice. There were no directive speech acts found in children's speech. The results of the research show that children's early speech repertoires are limited, transitional, and imperfectly language-like to a certain extent. Most of the linguistic forms acquired by children are expressions that lack the characteristics of syntactic combinations in adult language. The most dominant types of directive speech acts that often appear in the speech of preschool aged children are the types of directive speech acts of questions and commands. These two types of directive speech acts are the most prominent and are widely used by children to ask, order, and ask to remind.